2018
DOI: 10.3389/fenrg.2018.00013
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Whole Biomasses in Pyridine Based Ionic Liquid at Low Temperature by 31P NMR: An Approach to Quantitatively Measure Hydroxyl Groups in Biomass As Their Original Structures

Abstract: In this study, the dissolution of biomass components-cellulose, hemicellulose, and lignin, and two whole biomasses-switchgrass and poplar in a pyridine based ionic liquid at a low temperature-50°C has been examined, which will provide an opportunity to explore the original structures of biomass components. The following phosphitylation, and 31 P NMR measurement could provide quantitative results for various hydroxyl groups, including aliphatic, condensed phenolic, guaiacyl phenolic, p-hydroxyl phenyl and carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Furthermore, Argyropoulos's group has developed various imidazole-type ionic liquids to dissolve and characterize cellulose and the whole plant cell wall at elevated temperatures (~80-100°C) via quantitative 31 P NMR analysis [102][103][104][105] . In a recent study, Ben's group reported that a pyridine-based ionic liquid, 1-allyl-3-butylpyridinium chloride, was capable of dissolving the whole biomass at low temperature (50°C) and could be used in conjunction with the 31 P NMR methodology, thus providing a promising approach to quantitatively assess the hydroxyl groups in biomass as their original structures 106 . The broad applicability of this technique within the biorefinery research community is demonstrated in the following section.…”
Section: Nature Protocolsmentioning
confidence: 99%
“…Furthermore, Argyropoulos's group has developed various imidazole-type ionic liquids to dissolve and characterize cellulose and the whole plant cell wall at elevated temperatures (~80-100°C) via quantitative 31 P NMR analysis [102][103][104][105] . In a recent study, Ben's group reported that a pyridine-based ionic liquid, 1-allyl-3-butylpyridinium chloride, was capable of dissolving the whole biomass at low temperature (50°C) and could be used in conjunction with the 31 P NMR methodology, thus providing a promising approach to quantitatively assess the hydroxyl groups in biomass as their original structures 106 . The broad applicability of this technique within the biorefinery research community is demonstrated in the following section.…”
Section: Nature Protocolsmentioning
confidence: 99%
“…On the other hand, even though cellulose content in SEL was very similar to AHL, the lower hemicellulose and higher lignin content led to minor crosslinking. This fact occurs as a consequence of the higher hydroxyl content of both cellulose and hemicellulose [64]andthenoticeable steric impedance provided by lignin structure, which reduce isocyanate reactivity to the biopolymer [15,23]. In general, the higher the lignin content, the greater hindrance to promote crosslinking.…”
Section: Nco-functionalized Lignins Characterizationmentioning
confidence: 99%
“…Lignocellulosic fibers usually have higher strength than TPS, and the strong interfacial interaction between the fibers and the matrix, caused by the chemical similarity of the starch and the cellulose fiber, results in significant improvements in the mechanical properties. [52] However, the results observed in this work can be attributed to the higher content of hemicellulose in relation to cellulose in BSG, [22] which have fewer available hydroxyl groups to interact with starch due to its branched structure, [53] as well as to the presence of other non-cellulosic compounds in BSG. [25] Nonetheless, the fact that the tensile strength did not decrease as reported for other polymer matrices such as polycaprolactone [32,33] and polypropylene [35] is promising, suggesting compatibility between TPS and BSG.…”
Section: Mechanical Propertiesmentioning
confidence: 74%